Bioactive Loaded Novel Nano-Formulations for Targeted Drug Delivery and Their Therapeutic Potential - Sapna Kumari; Anju Goyal; Eda Sönmez Gürer; Evren Algın Yapar; Madhukar Garg; Meenakshi Sood; Rakesh K. Sindhu (MDPI AG, 2022)
Plant-based medicines have received a lot of attention in recent years. Such medicines have been employed to treat medical conditions since ancient times, and in those times only the observed symptoms were used to determine dose accuracy, dose efficacy, and therapy. Rather than novel formulations, the current research work on plant-based medicines has mostly concentrated on medicinal active phytoconstituents. In the past recent decades, however, researchers have made significant progress in developing "new drug delivery systems" (NDDS) to enhance therapeutic efficacy and reduce unwanted effects of bioactive compounds. Nanocapsules, polymer micelles, liposomes, nanogels, phytosomes, nano-emulsions, transferosomes, microspheres, ethosomes, injectable hydrogels, polymeric nanoparticles, dendrimers, and other innovative therapeutic formulations have all been created using bioactive compounds and plant extracts. The novel formulations can improve solubility, therapeutic efficacy, bioavailability, stability, tissue distribution, protection from physical and chemical damage, and prolonged and targeted administration, to name a few. The current study summarizes existing research and the development of new formulations, with a focus on herbal bioactive components.